Geoinformation service of soil quality evaluation - Кохан, Світлана Станіславівна; Москаленко, Антоніна Анатоліївна; Шило, Любов Григорівна (Eastern-European Journal of Enterprise Technologies, 2013)
The structure of geospatial database (GDB) in the form of a set of models (conceptual and logical) was developed in the study. The conceptual model of GDB is constructed on the basis of the unified modeling language UML (Unified Modeling Language). Physical implementation of the model for ensuring the qualitative evaluation of soil is shown. The paper gives the analysis of the use of various interpolators (distance weighting, bicubic spline, universal kriging) with the purpose to obtain digital continuous surfaces on the example of the humus content in soils. Significant difference in the application of various interpolators was not found. The GRID-model, obtained on the basis of the data of agrochemical inspection of soils was used as the digital image of the link. Interpolation as a component of geoinformation mapping can be effectively used for the reduction of the cost of agrochemical inspections due to the optimization of the number of soil samples